The Influence of the Madrasah Principal's Leadership Style on Teacher Performance at Islamic Senior High School of Miftahul Ulum Tanggul Jember - Achmad Fauzi; Khotibul Umam; Rusydi Baya'gub (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to find out and reveal about the leadership of school/madrasah principals and teacher performance and to analyze whether or not there was a relationship between the democratic leadership style of the madrasah head and teacher performance, to know the relationship between the leadership style and the participation of the madrasah head and teacher performance, to find out the relationship between the autocratic leadership style of the head. madrasah and teacher performance, knowing the relationship between the leadership style of the free control madrasa head and teacher performance, and knowing the relationship between leadership style and teacher performance. The research method uses a quantitative approach and a questionnaire is used as a research instrument. Data analysis used descriptive and correlation analysis techniques. Based on the results of the study, it was revealed that the leadership style of the madrasa head consisting of autocratic, participation, democracy and free control was quite good, with the frequency level of the leadership style used being democratic, participation, free and autocratic control. This leadership has a significant impact on good teacher performance in carrying out their duties and responsibilities such as planning, implementing and assessing learning well; there is a significant positive correlation to teacher performance obtained from the democratic leadership style of the madrasa head; there is a significant positive correlation of teacher performance arising from the participatory leadership style of the madrasa principal; there is a significant positive relationship between the free control teacher's leadership style and teacher performance; and there is a significant positive relationship between the principal's leadership style and teacher performance